SUSTAINABILITY ANALYSIS AND THE ROLE OF ENFORCEMENT LAW RELATING TO THE SILAT COLLEGE MONUMENT IN BOJONEGORO DISTRICT, EAST JAVA - Putra, Reza Ananda; Handayani, Tri Astuti; Mansur, Mochamad (Justisi: Jurnal Ilmu Hukum, 2025)
Pencak silat is a martial arts method created by the Indonesian people for protect yourself from danger. Pencak silat schools in Indonesia are synonymous with tugu universities which is the identity of a pencak silat school near the area with the symbol of a particular college. The existence of a martial arts monument can give rise to prolonged conflict between universities due to social jealousy and displeasure between other martial arts schools, to the detriment of civilians who live around the monument the martial arts. On the basis of frequent clashes due to pencak silat monuments made the governor of east java give an appeal to put in order the university monuments martial arts. Then the east java provincial government through the east java bakesbangpol issued an appeal for independently dismantle the martial arts school monument. The aim of this research is to determine the sustainability of the silat monument control program and to determine the role of law enforcement in controlling silat college monuments in Bojonegoro district, east java. The researcher used qualitative research methods with a type of empirical normative legal research.